(untitled) (Research, Society and Development, 2021)
Down syndrome results from the presence of 3 chromosomes 21, occurring at the time of conception of a baby who, instead of having 46, will have 47 chromosomes in their cells, presenting motor, language and cognitive alterations. Even with these changes, children with Down Syndrome cannot be treated as sick people, but as a human condition. The general objective of this research is to analyze what are the benefits of speech therapy intervention in babies with Down Syndrome. The methodology used consisted of a systematic review. The databases consulted were BIREME, LILACS, PubMed and SciELO, including studies published between the years 2015 to 2020. The descriptors used were: Down’s syndrome; Speech therapy; Early stimulation. After the search, five articles were selected for analysis. As a result, all the studies reviewed were affirmative of the importance of early stimulation for development, not only motor but also global for the child with Down Syndrome. Thus, it is concluded that speech therapy stimulation in the first months of life is able to favor the development of receptive and expressive language, the oral motor sensory system, stomatognathic functions and aspects of cognitive development, providing greater independence.